Implememtasi Akad Wakalah Bi Al- Istithmar Dalam Strategi Penghimpunan Dana Perbankan Syariah : Studi Kasus Di Kabupaten Bengkalis - nafra Ramadhani (UNCANG : Journal of Sharia Banking and Islamic Finance, 2026)
This study aims to examine the implementation of the Wakalah bi al-Istithmar contract within the fund-raising strategies of Islamic banks in Bengkalis Regency. Employing a qualitative library research method, the study relies on analyses of DSN-MUI (National Sharia Council-Indonesian Ulema Council) fatwas, Islamic banking regulations, books, scholarly journals, and other relevant literature. The findings reveal that the *Wakalah bi al-Istithmar* contract represents a novel innovation in Islamic banking fund-raising products. Essentially, the bank is authorized by the customer to manage their investment funds in accordance with Sharia principles. The process involves opening an account, signing the contract, managing funds through Sharia-compliant investment instruments, and ensuring oversight based on DSN-MUI Fatwas No. 126 of 2019 and No. 152 of 2022. Regarding fund-raising strategies, banks utilize educational promotions, leverage digital technology, and establish partnerships with institutions and communities. However, challenges persist, such as low Sharia financial literacy, competition with conventional banks, and a lack of public understanding regarding this new contract. Nevertheless, significant opportunities exist due to the Muslim majority population, the growing regional economy, and supportive regulations. In conclusion, the Wakalah bi al-Istithmar contract holds effective potential for increasing Third-Party Funds (DPK), strengthening the competitiveness of Islamic banking, and supporting the development of the Sharia economy in Bengkalis Regency. Penelitian ini bertujuan menganalisis implementasi akad Wakalah bi al-Istithmar dalam strategi penghimpunan dana perbankan syariah di Kabupaten Bengkalis. Penelitian menggunakan metode studi kepustakaan dengan pendekatan kualitatif melalui analisis terhadap peraturan, fatwa, literatur ilmiah, dan sumber sekunder yang relevan. Hasil penelitian menunjukkan bahwa akad Wakalah bi al-Istithmar merupakan inovasi produk penghimpunan dana yang menempatkan nasabah sebagai muwakkil dan bank sebagai wakil yang diberi kuasa untuk mengelola dana pada instrumen investasi sesuai prinsip syariah. Mekanisme pelaksanaannya meliputi pembukaan rekening, penandatanganan akad, penempatan dana pada instrumen investasi syariah, serta pengawasan berdasarkan Fatwa DSN-MUI Nomor 126 Tahun 2019 dan Fatwa DSN-MUI Nomor 152 Tahun 2022. Strategi penghimpunan dana dilakukan melalui promosi edukatif, pemanfaatan teknologi digital, serta kerja sama dengan instansi dan komunitas masyarakat. Implementasinya masih menghadapi kendala berupa rendahnya literasi keuangan syariah, terbatasnya pemahaman masyarakat terhadap karakteristik akad, dan kuatnya persaingan dengan perbankan konvensional. Meskipun demikian, besarnya populasi Muslim, pertumbuhan kegiatan ekonomi daerah, dan dukungan regulasi memberikan peluang bagi pengembangan produk tersebut. Akad Wakalah bi al-Istithmar berpotensi meningkatkan Dana Pihak Ketiga, memperkuat daya saing perbankan syariah, serta mendukung perkembangan ekonomi syariah di Kabupaten Bengkalis.